"What would you do if I die?": A Comparative Study of Death in China and Iceland - Theresia Mita Erika 1989- (2022)
Death is an essential part of life that bring purpose and meaning to it. The experience of death, however, concerns the bereaved almost more than the deceased individual themselves due to the emotional impact and responsibilities in its aftermath. This thesis endeavors to understand why we do what we do when a loved one dies in the hopes to find feasible ways to alleviate the suffering that follows, within the scope of life in Iceland. By focusing the research on literature available in English and Icelandic, the thesis attempts to do a comparative analysis between China (including Chinese diaspora) and Iceland. Official statements from the government and newspaper articles aided in the research on current practices and social issues. Academic journals provided a deeper understanding on relevant cultural issues and public sentiment. The research finds that China’s long and colorful history allowed tradition and folk beliefs to play a vital role in the construction of the perception of death and the afterlife in Chinese communities. Although old traditions still greatly influence death related customs to this day, modern societal factors have pushed urban Chinese community to take a more proactive role in planning the direction of their death journey. On the other hand, homogeneity in the Icelandic population led to the secularization of their institutions and society. These factors gave way to increased flexibility in death customs, which in turn presents an opportunity for new cultures and customs to emerge in the society. In the face of increasingly uncertain times, the results of this research suggest the adoption of personal initiative to discuss and plan end-of-life affairs, as seen in urban Chinese communities, as a potential solution to proactively lighten the burden on the bereaved in Iceland. Keywords: Death, funeral, end-of-life customs, China, Iceland, obituary, death preparation